Synthesis and Characterization of Iron Oxide Nanoparticles Using Syzygium aromaticum Extracts and their Activity on Organic Dye and Phytopathogen - Garba Ahmad, Rabiu; Kumar, Vineet (Asian Journal of Chemistry, 2021)
In present study, biosynthesis of iron oxide nanoparticles using clove (Syzygium aromaticum) extracts was performed and characterized. The activity of the biosynthesized iron oxide nanoparticles was evaluated against phytopathogen (Colletotrichum falcatum) and the result showed that the biogenic nanoparticles produced antifungal activity on the test organism. The photocatalytic activity of the present study revealed a rapid and efficient degradation of methylene blue within 0.5 h.